2015
DOI: 10.3354/ab00605
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the submerged macrophyte Vallisneria natans to elevated CO2 and temperature

Abstract: Inorganic carbon and temperature are 2 important factors that regulate the growth of submerged macrophytes. However, experimental evidence regarding the eco-physiological changes that occur in submerged macrophytes in response to elevated CO 2 and temperature is still limited. To investigate how the submerged macrophyte Vallisneria natans (Hydrocharitaceae), a common species in the waters of the middle and lower reaches of the Yangtze River, responds to these factors, we conducted a mesocosm experiment using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
2
12
0
1
Order By: Relevance
“…In this study CO 2 , DOC and, to a smaller extent, flow velocity (all potential effects of climate change) had strong effects on the growth and development of B. erecta, which is consistent with what was found in literature (Steinberg et al, 2006;McElarney et al, 2010;Cao and Ruan, 2015;Reitsema et al, 2020). Macrophytes that grew in the wet climate change scenario with increased heavy precipitation intensity (HD-HC-HF) had a higher RGR, more biomass, shorter stems, a higher root:shoot ratio, lower N content and higher P content than the plants growing in the no climate change scenario.…”
Section: Discussionsupporting
confidence: 93%
“…In this study CO 2 , DOC and, to a smaller extent, flow velocity (all potential effects of climate change) had strong effects on the growth and development of B. erecta, which is consistent with what was found in literature (Steinberg et al, 2006;McElarney et al, 2010;Cao and Ruan, 2015;Reitsema et al, 2020). Macrophytes that grew in the wet climate change scenario with increased heavy precipitation intensity (HD-HC-HF) had a higher RGR, more biomass, shorter stems, a higher root:shoot ratio, lower N content and higher P content than the plants growing in the no climate change scenario.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the ramet number was increased at 25/15°C and then diminished with the temperature rose in non‐saline conditions. Similar to our results, an appropriate increase in temperature will increase the ramet number of submerged macrophyte Vallisneria natans (Cao and Ruan 2015). For one thing, temperature elevation can increase the activity of photosynthetic, enzymes, and carbonic anhydrase, which likely caused the increases in ramet number in our experiment (Olesen and Madsen 2000).…”
Section: Discussionsupporting
confidence: 89%
“…The influence of salinity on plant growth generally showed that seedling growth is inhibited with the increase in salinity, which is mainly manifested by the reduction in growth traits and biomass accumulation (Pompeiano et al 2016, MacTavish and Cohen 2017). Meanwhile, the biomass accumulation and clonal reproductive capacity of salt marsh plants would increase with the rising temperature (Johnson and Thornley 1985, Cao and Ruan, 2015, Zhang et al 2018). Higher temperature may also enlarge or reduce the influence of salinity on plant growth, but the relevant evidence is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…), increase growth (Yan et al . ; Cao & Ruan ), and alter allocation of biomass (Cao & Ruan ). Of note, however, macrophytes have been found to self‐limit based on daily fluctuations in pH (i.e.…”
Section: Potential Effects Of Changing Pco2 On Freshwater Biotamentioning
confidence: 99%